Analysis of Metal Contaminants and Wear in Lubricating Oil of Two-Stroke Diesel Engines Based on ASTM Testing Standards - Mustopa Kamal; Ade Hermawan; Achmad Syarifudin; I Ketut Daging; M Yusuf Yusuf Syam; Raedy Anwar S; Angga Putra Jaya (Faculty of Engineering, Universitas Muhammadiyah Jakarta, 2025)
Common issues in diesel engines include lubricating oil contamination and metal wear, which significantly degrade oil quality. This study analyzes contamination and metal wear in the lubricating oil of a two-stroke diesel engine using American Standard Testing and Material (ASTM) methods. Data were obtained from 130 mL lubricating oil samples taken from a main engine and tested according to ASTM standards. The observed variables included independent factors (contamination and metal wear levels) and the dependent variable (lubricating oil quality), all analyzed in a laboratory. Testing methods comprised ASTM D445-21e2/ASTM D2896-21 (Cannon CT-500 Series II viscometer), ASTM D5185-18 (ICP-OES 5100 VDC spectrometer), and ASTM E2412-18 (Thermo Scientific Nicolet FTIR spectrometer), conducted at PT Petrolab Services Laboratory. Results from oil samples used for 7,744.5 and 10,576.5 operational hours indicated the presence of sodium (Na) and silicon (Si), suggesting a coolant leak containing salt. Furthermore, component friction generated significant wear metal particles—iron (Fe), copper (Cu), aluminum (Al), lead (Pb), and chromium (Cr)—which were trapped in the oil filter. This accumulation decreased lubricant quality by forming wear debris and sludge, potentially clogging lubrication channels. It was concluded that the lubricating oil quality degraded over four months of use. This issue can be mitigated by inspecting and repairing or replacing contaminated or worn parts, partially draining the oil via the underdrain tap during circulation, and topping up with the same oil grade.